Distance Learning and Global Demand - Kemp, Neil (International Higher Education, 2020)
Are international students losing their appetite for distance learning (DL) degrees? Recent poor growth in global enrollments does seem counterintuitive, given previous predictions that suggested a future where information technology and MOOCs would enhance outreach, offer greater student choice, and result in new enrollments. Is this a short-term pattern or evidence of a long-term trend? (In this paper, DL refers only to programs in which a full degree program, not parts, are followed through DL arrangements.)